Social Media Strategies for Gender Artivism: A Generation of Feminist Spanish Women Illustrator Influencers - Palomo-Domínguez, Isabel; Jiménez-Marín, Gloria; Sánchez-Gey Valenzuela, Nuria (Information & Media, 2023)
Nowadays, social networks play a central role in communication media. In this scenario, analysing the gender awareness fostered by the influencers is crucial.The research explores the female representation portrayed by eight Spanish influencers who address the gender approach from graphic communication. All of them are women illustrators, cover topics related to gender, and use similar communication strategies.The methodology includes three complementary techniques: first, desktop study to compare the illustrators’ profiles; second, content analysis to delve into the topics addressed and their artivism; third, a Delphi method to assess their contribution to promoting gender egalitarian values, in which experts specialising in communication, philosophy, sociology, psychology, and politics participate.The results show that feminism is a prominent topic in their publications, stimulating a feeling of sisterhood among women, their core target. From a generational perspective, the influence of their message is more significant on millennials and centennials. Conclusions confirm that social media characteristics, artivism, content hybridisation and transmediality enhance their feministic discourse. Future lines of research may focus on identifying other channels and communication strategies more influential for broad target groups, especially men and generations older than millennials, since these external audiences seem crucial to spread gender awareness.
Keywords: Feminism; Social Media; Artivism; Transmediality; Illustrators